Densities of internally mixed organic-inorganic particles from mobility diameter measurements of aerodynamically classified aerosols. Issue 8 (22nd June 2022) - Vokes, Elinor T.; Lewis, Ernie R.; Johnson, Andrew L.; Cotterell, Michael I.
Abstract: Accurate knowledge of particle density is essential for many aspects of aerosol science. Yet, density is often characterized poorly and incompletely for internally mixed particles, particularly for dry particles, with previous studies focused primarily on deliquescent (aqueous) droplets. Instead, densities for dry internally mixed particles are often inferred from mass composition measurements in combination with predictive models assuming ideal mixing, with the accuracy of such models not estimated. We determined particle densities from mobility diameter measurements (using a Scanning Mobility Particle Sizer, SMPS) for dried particles classified by their aerodynamic size (using an Aerosol Aerodynamic Classifier, AAC) for a range of two-component organic-inorganic particles containing known proportions of organic and inorganic species. We examined all permutations of mixing between four different organic (water soluble nigrosin dye, citric acid, polyethylene glycol-400, and ascorbic acid) and three different inorganic (sodium chloride, ammonium sulfate, and sodium nitrate) species. The accuracy and precision in our measured particle densities were ∼5% and ∼1%, respectively, for nonvolatile particles. Substantial deviations in particle density from ideal mixing (up to 20%) were observed. We tested descriptions of the non-ideal mixing for our systems by representing the volume change of mixing using Redlich-Kister (RK) polynomials in terms of mass fraction or in terms of mole fraction, with both approaches performing similarly. Graphical Abstract: UF0001